The penal implications of austerity: Italian punishment in the wake of the Eurozone crisis - Gallo, Zelia A. (European journal of criminology, 2019)
The article discusses the implications of the Eurozone crisis for Italian penality. It begins by analysing the ‘politics of austerity’ – the economic reforms and new political mode entrenched by the Eurozone crisis. It then reflects upon the penal implications of such changes, focusing on the conceptual links between state–citizen relations, political institutional arrangements, and punishment in Italy. The article argues that Italy will continue to display an alternation of punitiveness and moderation. However, the meaning and contours of both punitiveness and moderation are changing. Punitiveness is likely to be exacerbated as punishment is used to impose cohesion on an ever more fragmented polity. Moderation, far from being a collective good and ‘public philosophy’, is likely to become a narrow, stratified and personalistic good. The article urges us to consider whether austerity may be engendering similar dynamics across other EU polities.